A new economy-durability tool design to improve joint quality of titanium alloy friction stir welds - S. Cong; L.H. Wu; Z.W. Wang; F.F. Wang; X. Zhang; X.C. Du; P. Xue; F.C. Liu; D.R. Ni; B.L. Xiao; Z.Y. Ma (Journal of Materials Research and Technology)
For years, friction stir welding (FSW) of Ti alloys has been blocked by the economy-durability trade-off of dedicated tools and bottom defects formed in the joints. In this work, an economy-durability tool was developed to achieve high-quality FSW joint of a medium-thickness plate Ti–6Al–4V alloy. The properties and wear of a newly developed low-Re content W-7Re–La2O3 (ppm) alloy tool were comprehensively evaluated, in comparison with those for the tools made up of conventional materials of Co-based, Ni-based high-temperature alloys and high-Re content W-25Re alloy. Severe wear and deformation occurred in the both high-temperature alloy tools, while similar excellent wear and deformation resistance existed for both W-7Re–La2O3 (ppm) and W-25Re tool. However, defects were consistently observed at the bottom of the joints obtained with conventional tool with flat-type end pin or convex shoulder. The material flow in the joints was improved by new tool with a concave shoulder and a spherical pin. The results of an industrial computerized tomography non-destructive analysis showed that the new tool changed the material flow of the joint. The stress on the bottom material changed from being squeezed to the sides to being pressed down to the bottom, which enabled a uniform material flow at the bottom and prevented bottom defect of the joint. As a result, a defect-free joint with the joint strength of 1015 MPa equal to that of the base material was achieved. This work provides a new design strategy of economy-durability tool to improve the joint quality of titanium alloys.